Direct, Metal-Free Synthesis of Benzyl Alcohols and Deuterated Benzyl Alcohols from p-Toluenesulfonylhydrazones Using Water as Solvent - García-Muñoz, Ángel; Ortega-Arizmendi, Aldo I.; García-Carrillo, Mario A.; Díaz, Eduardo; Gonzalez-Rivas, Nelly; Cuevas-Yañez, Erick (Synthesis, 2012)
A novel library of diverse alcohols was synthesized by metal-free couplings of diazoalkanes derived from p-toluenesulfonylhydrazones to water under reflux and microwave conditions, in high yields. In addition, this protocol was successfully applied in the synthesis of deuterium-labeled alcohols using deuterium oxide.
Keywords: alcohols; deuterated alcohols; p-toluenesulfonylhydrazones; coupling